Pneumococcal Septic Arthritis among Adults, France, 2010–2018 - Farida Hamdad; Nadim El Bayeh; Gabriel Auger; Olivia Peuchant; Frédéric Wallet; Raymond Ruimy; Florence Reibel; Christian Martin; Marie-Cécile Ploy; Frédéric Robin; Chrislène Laurens; Philippe Lanotte; et al. (Emerging Infectious Diseases)
Streptococcus pneumoniae infection is considered an uncommon cause of arthritis in adults. To determine the clinical and microbiological characteristics of pneumococcal septic arthritis, we retrospectively studied a large series of cases among adult patients during the 2010–2018 conjugate vaccine era in France. We identified 110 patients (56 women, 54 men; mean age 65 years), and cases included 82 native joint infections and 28 prosthetic joint infections. Most commonly affected were the knee (50/110) and hip (25/110). Concomitant pneumococcal infections were found in 37.2% (38/102) and bacteremia in 57.3% (55/96) of patients, and underlying conditions were noted for 81.4% (83/102). Mortality rate was 9.4% (8/85). The proportion of strains not susceptible to penicillin was 29.1% (32/110). Of the 55 serotyped strains, 31 (56.4%) were covered by standard pneumococcal vaccines; however, several nonvaccine serotypes (mainly 23B, 24F, and 15A) had emerged, for which susceptibility to β-lactams was low.